Hospes: The Wabash Center as a Site of Transformative Hospitality - Jones, Carolyn M. (Teaching theology and religion, 2007)
The Wabash Center for Teaching and Learning in Theology and Religion is a place of hospitality and its staff the epitome of the “good host.” This essay explores the meaning of hospitality, including its problematic dimensions, drawing on a number of voices and texts: Jacques Derrida's Of Hospitality; Henri M. Nouwen's Reaching Out: The Three Movements of the Spiritual Life, N. Lynne Westfield's Dear Sisters: A Womanist Practice of Hospitality, Arthur Sutherland's I Was a Stranger: A Christian Theology of Hospitality, and Kathleen Norris's “Hospitality.” Beginning with the claim that hospitality is concerned with power and grace, the essay explores the relationship between hospitality and teaching, and the modes by which the Wabash Center helps teachers both find their identities and heal.